Trombospondina na hipoplasia induzida por desnutrição protéica - VITURI, Cidônia de Lourdes; ALVAREZ-SILVA, Márcio; TRENTIN, Andréa Gonçalves; TRAMONTE, Vera Lúcia Cardoso Garcia; BORELLI, Primavera (Revista de Nutrição, 2023)
Objective The objective of the present study was to measure the concentration of bone marrow extracellular matrix thrombospondin in mice, following hypoplasia induced by protein malnutrition. Methods Two-month-old male Swiss mice were submitted to protein malnutrition by way of a low-protein diet containing 4.0% casein until they lost 20.0% of their original body weight, while the control group mice were fed 14.0% casein for 15 days. The bone marrows of the animals were aspirated and transferred to phosphate-buffered saline tubes for extraction. The extracellular matrix protein was analyzed by 7.5% SDS-PAGE and thrombospondin by Enhanced Chemiluminescence Light Western blotting. Results The amount of thrombospondin was 30% higher in the undernourished samples when compared to the control samples. Conclusion This study suggests that the hypoplasia induced by protein malnutrition probably alters the functioning of the bone marrow microenvironment resulting in a higher thrombospondin concentration.